Regulation of the Fanconi Anemia DNA Repair Pathway by Phosphorylation and Monoubiquitination - Masamichi Ishiai (MDPI AG, 2021)
The Fanconi anemia (FA) DNA repair pathway coordinates a faithful repair mechanism for stalled DNA replication forks caused by factors such as DNA interstrand crosslinks (ICLs) or replication stress. An important role of FA pathway activation is initiated by monoubiquitination of FANCD2 and its binding partner of FANCI, which is regulated by the ATM-related kinase, ATR. Therefore, regulation of the FA pathway is a good example of the contribution of ATR to genome stability. In this short review, we summarize the knowledge accumulated over the years regarding how the FA pathway is activated via phosphorylation and monoubiquitination.